TRANSISI DEMOKRASI DAN TRANSFORMASI GENDER. STUDI KASUS: TERPILIHNYA MICHELLE BACHELET SEBAGAI PRESIDEN PEREMPUAN PERTAMA DI CHILE - Rico Suherman; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This study discusses the election of Michelle Bachelet as Chile's first female president. Chile is a conservative country and embrace the patriarchal lineage, so that automatically marginalized role of women. In the midst of such a country, Michelle Bachelet is able to compete with men and won elections in 2006. Michelle Bachelet's victory is quite interesting, considering that previously no women to be the number one in Chile. To that end, the formulation of the problem in this research is what factors are encouraging victories Michelle Bachelet as Chile's first female president.Theoretical framework in this study include democratic transition, transformation of gender, participation and influence on the legitimacy of women's individual capability. Democratic transitionis used to explain the collapse of the authoritarian regimeled by Augusto Pinochet that impact on women. Gender transformation is used to describe the process of acceptance of women in a broaderscope. Participation and legitimacy to women used to describe the impact of gender transformation. Individual capacity in this paperis used to indicate modality Michelle Bachelet to be able to make it asthe first woman President in Chile.The writing is at last reaching a hypothesis that the transition to democracy that occurredin Chileled to the transformation of gender that can open upopportunities for women to participatein politics and individual factors Michelle Bachelet who do havethe capital to become a President. Their conclusion that the hypothesisis proven,but there are other factors at the state level that influence, namely the dominance of left ist parties in Chile.Keywords: Gender, President of Women, politicalparticipation, party left